Sulfated carboxymethyl cellulose and carboxymethyl κ-carrageenan immobilization on 3D-printed poly-ε-caprolactone scaffolds differentially promote pre-osteoblast proliferation and osteogenic activity - Abbasi-Ravasjani, Sonia; Seddiqi, Hadi; Moghaddaszadeh, Ali; Ghiasvand, Mohammad-Ehsan; Jin, Jianfeng; Oliaei, Erfan; Bacabac, Rommel Gaud; Klein-Nulend, Jenneke (Frontiers in Bioengineering and Biotechnology, 2022)
Lack of bioactivity of three-dimensional (3D)-printed poly-є-caprolactone (PCL) scaffolds limits cell-material interactions in bone tissue engineering. This limitation can be overcome using surface-functionalization by glycosaminoglycan-like anionic polysaccharides, e.g. carboxymethyl cellulose (CMC), a plant-based carboxymethylated, unsulfated polysaccharide, and κ-carrageenan, a seaweed-derived sulfated, non-carboxymethylated polysaccharide. Sulfation of CMC and carboxymethylation of κ-carrageenan critically improve their bioactivity, but how sulfated carboxymethyl cellulose (SCMC) and carboxymethyl κ-carrageenan (CM-κ-Car) affect the osteogenic differentiation potential of pre-osteoblasts on 3D-scaffolds is still unknown. Here we aimed to assess the effects of surface-functionalization by SCMC or CM-κ-Car on physicochemical and mechanical properties of 3D-printed PCL scaffolds, as well as the osteogenic response of pre-osteoblasts. MC3T3-E1 pre-osteoblasts were seeded on 3D-printed PCL scaffolds either or not functionalized by CM-κ-Car (PCL/CM-κ-Car), or SCMC (PCL/SCMC), and cultured up to 28 days. The scaffolds’ physicochemical and mechanical properties, and pre-osteoblast function were assessed experimentally and by finite element modeling. Surface-functionalization by SCMC and CM-κ-Car did not change scaffold geometry and structure, but similarly increased surface roughness and hardness, as well as decreased water contact angle and elastic modulus. Finite element modeling showed that maximal von Mises stress for 2% compression strain did not exceed yield stress for bulk material in all scaffolds. Surface-functionalization by SCMC decreased Runx2 and Dmp1 expression, while surface-functionalization by CM-κ-Car increased Cox2 expression at day 1. Surface-functionalization by SCMC most strongly enhanced pre-osteoblast proliferation and collagen production, while CM-κ-Car most significantly increased alkaline phosphatase activity and mineralization after 28 days. In conclusion, surface-functionalization by SCMC or CM-κ-Car of 3D-printed PCL-scaffolds enhanced pre-osteoblast proliferation and osteogenic activity, likely due to increased surface roughness and hydrophilicity. Surface-functionalization by SCMC most strongly enhanced cell proliferation, while CM-κ-Car most significantly promoted osteogenic activity, suggesting that surface-functionalization by CM-κ-Car may be more promising, especially in the short-term, for in vivo bone formation.